Involvement of calmodulin and calmodulin-like proteins in plant responses to abiotic stresses - Zeng, Houqing; Xu, Luqin; Singh, Amarjeet; Wang, Huizhong; Du, Liqun; Poovaiah, B. W. (Frontiers in Plant Science, 2015)
Transient changes in intracellular Ca2+ concentration have been well recognized to act as cell signals coupling various environmental stimuli to appropriate physiological responses with accuracy and specificity in plants. Calmodulin (CaM) and calmodulin-like proteins (CMLs) are major Ca2+ sensors, playing critical roles in interpreting encrypted Ca2+ signals. Ca2+-loaded CaM/CMLs interact and regulate a broad spectrum of target proteins such as channels/pumps/antiporters for various ions, transcription factors, protein kinases, protein phosphatases, metabolic enzymes and proteins with unknown biochemical functions. Many of the target proteins of CaM/CMLs directly or indirectly regulate plant responses to environmental stresses. Basic information about stimulus-induced Ca2+ signal and overview of Ca2+ signal perception and transduction are briefly discussed in the beginning of this review. How CaM/CMLs are involved in regulating plant responses to abiotic stresses are emphasized in this review. Exciting progress has been made in the past several years, such as the elucidation of Ca2+/CaM-mediated regulation of AtSR1/CAMTA3 and plant responses to chilling and freezing stresses, Ca2+/CaM-mediated regulation of CAT3, MAPK8 and MKP1 in homeostasis control of ROS signals, discovery of CaM7 as a DNA-binding transcription factor regulating plant response to light signals. However, many key questions in Ca2+/CaM-mediated signaling warrant further investigation. Ca2+/CaM-mediated regulation of most of the known target proteins is presumed based on their interaction. The downstream targets of CMLs are mostly unknown, and how specificity of Ca2+ signaling could be realized through the actions of CaM/CMLs and their target proteins is largely unknown. Future breakthroughs in Ca2+/CaM-mediated signaling will not only improve our understanding of how plants respond to environmental stresses, but also provide the knowledge base to improve stress-tolerance of crops.